2007
DOI: 10.1126/science.1144706
|View full text |Cite
|
Sign up to set email alerts
|

A Common Fold Mediates Vertebrate Defense and Bacterial Attack

Abstract: Proteins containing membrane attack complex/perforin (MACPF) domains play important roles in vertebrate immunity, embryonic development, and neural-cell migration. In vertebrates, the ninth component of complement and perforin form oligomeric pores that lyse bacteria and kill virus-infected cells, respectively. However, the mechanism of MACPF function is unknown. We determined the crystal structure of a bacterial MACPF protein, Plu-MACPF from Photorhabdus luminescens, to 2.0 angstrom resolution. The MACPF doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
242
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(250 citation statements)
references
References 30 publications
7
242
0
1
Order By: Relevance
“…Our initial analysis suggested that all but 3 of 17 cancer-and late FHL-associated PRF mutants had no cytotoxic function when analyzed in vitro. However we also discovered, through mapping these mutations onto the predicted three dimension PRF structure (based on three crystallized MACPF proteins [31][32][33] ) that many of the mutants localized to a single subdomain at the top of the PRF monomer, the part furthest removed from the membrane-binding domains. 10 Intriguingly, in light of previous studies on A91V, 80 this common variant was also shown to map to the same subdomain and result in protein misfolding.…”
Section: Perforin Deficiency and Human Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial analysis suggested that all but 3 of 17 cancer-and late FHL-associated PRF mutants had no cytotoxic function when analyzed in vitro. However we also discovered, through mapping these mutations onto the predicted three dimension PRF structure (based on three crystallized MACPF proteins [31][32][33] ) that many of the mutants localized to a single subdomain at the top of the PRF monomer, the part furthest removed from the membrane-binding domains. 10 Intriguingly, in light of previous studies on A91V, 80 this common variant was also shown to map to the same subdomain and result in protein misfolding.…”
Section: Perforin Deficiency and Human Cancermentioning
confidence: 99%
“…However, in the year 2007-2008, three independent studies arrived at the same remarkable conclusion: despite sharing minimal amino acid sequence similarity, mammalian and other MACPF proteins are structurally related to bacterial cholesterol-dependent cytolysins (CDCs) and operate by an analogous mechanism. [31][32][33] These studies opened new horizons in studying MACPF proteins, as their membership with a large family of well-characterized proteins has finally been identified. Despite these advances, major milestones in MACPF research are yet to be reached, namely, the crystal structure of a pore-forming MACPF protein, the mechanism of pore formation and the structure of a pore.…”
Section: Perforin Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…These C-terminal domains vary in sequence and structure, but are consistently comprised almost entirely of β-pleated sheets, as in the case of the EGF-like and C2 domains of perforin, 21 the β-prism domains of the bacterial PluMACPF, 4 and the β-sandwich Ig domain of the CDCs. 22 Similarly, the C-termini of ApiPLPs are generally occupied by multiple copies of a predicted domain comprised of five β-strands, which we have termed ApiPLP C-terminal β-pleated sheet (APC-β) domains.…”
Section: Structurementioning
confidence: 99%
“…2,3 Exciting work over the past couple of years has provided additional insight into their molecular mechanism of action by revealing that the MACPF fold is shared with that of the cholesterol-dependent cytolysins (CDCs), an extensively studied family of bacterial pore-forming virulence factors. 4,5 Here we present an overview of the Apicomplexan PerforinLike Proteins (ApiPLPs) that have been identified in parasites for which genome sequence is available. It should be noted that apicomplexan genome sequencing efforts differ greatly in terms of completion, sequence coverage and quality of the gene predictions.…”
Section: Introductionmentioning
confidence: 99%